2007
DOI: 10.1379/csc-227r.1
|View full text |Cite
|
Sign up to set email alerts
|

Homologous cpn60 genes in Rhizobium leguminosarum are not functionally equivalent

Abstract: Many bacteria possess 2 or more genes for the chaperonin GroEL and the cochaperonin GroES. In particular, rhizobial species often have multiple groEL and groES genes, with a high degree of amino-acid similarity, in their genomes. The Rhizobium leguminosarum strain A34 has 3 complete groE operons, which we have named cpn.1, cpn.2 and cpn.3. Previously we have shown the cpn.1 operon to be essential for growth, but the two other cpn operons to be dispensable. Here, we have investigated the extent to which loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Sequence analysis followed by detailed promoter probe assays revealed that the groEL1 operon is regulated by RpoH-and HrcA-dependent mechanisms while groEL2 appears to be solely regulated by RpoH. Expectedly, groEL3 is induced by NifA and moderately repressed by HrcA (Rodriguez-Quinones et al 2005;Gould et al 2007b). These results therefore indicate that the essential chaperonin is expressed at the highest levels and the expression is tightly controlled by RpoH and HrcA.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis followed by detailed promoter probe assays revealed that the groEL1 operon is regulated by RpoH-and HrcA-dependent mechanisms while groEL2 appears to be solely regulated by RpoH. Expectedly, groEL3 is induced by NifA and moderately repressed by HrcA (Rodriguez-Quinones et al 2005;Gould et al 2007b). These results therefore indicate that the essential chaperonin is expressed at the highest levels and the expression is tightly controlled by RpoH and HrcA.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 99%
“…The presence of multiple copies of chaperonins immediately suggests differences in the regulation of expression or differences in function. The situation with R. leguminosarum apparently exhibits both the possibilities; the three chaperonin genes are regulated in a complex manner (George et al 2004;Gould et al 2007b), and the gene products exhibit divergent behavior in vivo (Ogawa and Long 1995;Ivic et al 1997;Gould et al 2007b) and in vitro (George et al 2004;Yeh et al 2002) as reviewed below. Expression studies on these chaperonin operons, however, revealed a complex picture.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 99%
“…Bacterial cells usually contain one copy of the groEL gene within the genome. However, approximately 20% of sequenced bacterial genomes were found to have duplicate or multiple copies of the groEL gene (10,11). The products of duplicated groEL genes have been reported to play divergent roles in various bacteria.…”
mentioning
confidence: 99%
“…In addition to rpoB, cpn60 (60 kDa chaperone; groEL) has been developed as a microbial ecological marker (Links et al, 2012) for human and plant microbiome studies (Oliver et al, 2008, Schellenberg et al, 2011, Chaban et al, 2014. Cpn60 is a better marker than 16S rRNA in samples with high host DNA content; however this gene is often duplicated (Johnson et al, 2015) and sometimes more non-identical copies are present in the genome (Gould et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to rpoB, cpn60 (60 kDa chaperone; groEL) has been developed as a microbial ecological marker (Links et al, 2012) for human and plant microbiome studies (Oliver et al, 2008, Schellenberg et al, 2011, Chaban et al, 2014. Cpn60 is a better marker than 16S rRNA in samples with high host DNA content; however this gene is often duplicated (Johnson et al, 2015) and sometimes more non-identical copies are present in the genome (Gould et al, 2007). The soil-selected population consisted of 118 strains obtained after direct soil cultivation and isolated using a semi-selective medium (Louvrier et al, 1995), followed by PCR-based screening of chromosomal (fnrN and glnII) and symbiotic markers (nodC and nifH).…”
mentioning
confidence: 99%